Distribution of Soil Organic Carbon along an Elevation Gradient on Kaba Volcano, Bengkulu Province, Indonesia - I Nyoman Candra; Denny Parta Wijaya; Rina Elvia (JOURNAL OF TROPICAL SOILS, 2026)
Climate change is a global issue largely driven by increasing atmospheric carbon dioxide levels. Many studies have focused on reducing CO2 emissions to mitigate its impacts. Volcanic soils are recognized for their high capacity to sequester carbon, second only to deep-sea reservoirs. However, limited research has examined soil organic carbon in volcanic soils on Kaba Volcano, Bengkulu, Indonesia. This study investigated the distribution of soil organic carbon along an elevation gradient on Kaba Volcano. Nine soil samples, both disturbed and undisturbed, were collected at a depth of 10 cm from three elevations: foothill, hillside, and hilltop. Undisturbed samples were taken using a 70-mm core cylinder to determine bulk density, while disturbed samples were collected with a shovel to analyze soil organic carbon, pH, and particle-size distribution. Soil organic carbon was measured using the Walkley–Black method, soil pH with a pH meter in KCl solution, and particle size using wet sieving and the pipette method. Results showed the highest soil organic carbon at the hillside, though not significantly different from the foothill, while the hilltop had the lowest content. Lower organic carbon at the hilltop may be related to drier conditions and reduced vegetation cover.